Smart hydrogels in tissue engineering and regenerative medicine - Oliveira, J. M. (2015)
“Smart” hydrogels, also variously referred as “intelligent”, “stimuli-responsive”, “stimuli-sensitive” or “environmentally-sensitive” hydrogels, are 3D hydrophilic network structures of polymer chains that are able to change their properties in response to environmental stimuli such as temperature, pH, light, magnetic and electric fields, and ionic strength or enzymatic environment. Systems with multiple responsive properties have also been developed combining two or more stimulus. Rapid and significant responses to changes to external stimuli are critical for the versatility of such “smart” hydrogels. That stimuli-responsive hydrogels are potentially beneficial for a diverse range of applications because the properties can be changed by the stimulus at the desired point and time. We will present our most recent and relevant reports dealing with the development, applications and processing of “smart” hydrogels, mainly in the context of tissue engineering and regenerative medicine.